Anaphylaxis in Elderly Patients—Data From the European Anaphylaxis Registry - Aurich, Stefanie; Dölle-Bierke, Sabine; Francuzik, Wojciech; Bilo, Maria Beatrice; Christoff, George; Fernandez-Rivas, Montserrat; Hawranek, Thomas; Pföhler, Claudia; Poziomkowska-Gȩsicka, Iwona; Renaudin, Jean-Marie; Oppel, Eva; Scherer, Kathrin; et al. (Frontiers in Immunology, 2019)
Background: Elicitors and symptoms of anaphylaxis are age dependent. However, little is known about typical features of anaphylaxis in patients aged 65 years or more. Methods: The data from the Network for Online Registration of Anaphylaxis (NORA) considering patients aged ≥65 (elderly) in comparison to data from adults (18 to 64 years) regarding elicitors, symptoms, comorbidities and treatment measures were analyzed. Results: We identified 1123 elderly anaphylactic patients. Insect venoms were the most frequent elicitor in this group (p<0.001), followed by drugs like analgesics and antibiotics. Food allergens elicited less frequently anaphylaxis (p<0.001). Skin symptoms occurred less frequently in elderly patients (77%, p<0.001). The clinical symptoms were more severe in the elderly (51% experiencing grade III/IV reactions), in particular when skin symptoms (p<0.001) were absent. Most strikingly, a loss of consciousness (33%, p<0.001) and preexisting cardiovascular comorbidity (59%, p<0.001) were more prevalent in the elderly. Finally, adrenaline was used in 30% of the elderly (versus 26% in the comparator group, p<0.001) and hospitalization was more often required (60% versus 50%, p<0.001). Discussion and conclusion: Anaphylaxis in the elderly is often caused by insect venoms and drugs. These patients suffer more often from cardiovascular symptoms, receive more frequently adrenaline and require more often hospitalization. The data indicate that anaphylaxis in the elderly tends to be more frequently life threatening and patients require intensified medical intervention. The data support the need to recognize anaphylaxis in this patient group, which is prone to be at a higher risk for a fatal outcome.